THE PROMINENT ISSUES OF SECOND LANGUAGE ACQUISITION OF STUDENTS IN ISLAMIC BOARDING SCHOOL AL-ITTIFAQIAH - Retno Indri Yustika (Program Studi Ekonomi Syariah, 2019)
The importance of studying the language leads many people, especially students to become masters in understanding the language which demands an advanced second language which is very prevalent today. Second language acquisition is the realm in which students not only understand their first language, but they also must be proficient in their second language (English and Arabic). SLA coverage in this case is its implementation in Islamic boarding school Al-IttiaqiyahIndralaya, where the issues are so prominent in the implementation of the second language (English and Arabic) that is related to the theory, the types of approach and crucial factor affecting the success of students in the second language acquisition itself.